KARAKTERISTIK SIFAT FISIK DAN KIMIA TANAH DI KAWASAN HUTAN LINDUNG SENTAJO KABUPATEN KUANTAN SINGINGI, PROVINSI RIAU - Pebriandi .; Omo Rusdiana; Muhamad Buce Saleh (JURNAL ILMU-ILMU KEHUTANAN, 2021)
Forest is an ecosystem based on the complexity of its components. One of the components of a forest is soil. The importance of soil for human survival and growth for trees. In this ,research we analyzed the physical and chemical characteristics of soil in Sentajo Protected Forest. Soil samples were taken using composite and ring samples techniques. Soil samples were taken from five plot points measuring 20 m x 20 m in two depth level namely, 0-20 cm and 20-40 cm. mixed evenly to get one composite soil mixture. The results of research in Sentajo Protected Forest showed that the land in Sentajo Protected Forest was classified as acidic with a value of 3.68 - 4.34 with organic C content that is classified as low to high and a low KTK value. Moreover, the physical characteristics of the soil in Sentajo Protected Forest were more sandy texture. The values of moisture content, bulk density and porosity at a depth of 0 - 20 cm were higher when compared to a depth of 20 - 40 cm.